The US trade policy towards the EC in the Tokyo round - Reinhard Rode (Intereconomics, 1979)
The seventh round of GATT negotiations was brought to a conclusion in the spring of this year. One of the objects for the USA was to correct the trend of world trade which had been to its disadvantage. Its main concern was to bring about a settlement of the trade relations with the western industrialized states and the EC in particular. Has the USA achieved these aims?
Keywords: 330; GATT